HEMOTHORAX FOLLOWING PENETRATING THORACIC INJURY (GUNSHOT WOUND) IN GERIATRIC PATIENT: A CASE REPORT AND EMERGENCY MANAGEMENT - Laksono, Gerardo AK; Erwin, Ferdinand; Sarvasti, Dyana; Tahalele, Paul L (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Penetrating chest trauma is highly lethal. Studies have reported up to 60% mortality depending on the mechanism of injury. While penetrating chest trauma is lesscommon than blunt trauma, it can be more deadly. High-velocity gunshot injury resulting inpenetrating thoracic trauma in geriatric patients poses a significant challenge for the traumaticsurgeon. Hemothorax is usually a consequence of penetrating chest trauma. It can be caused byintercostal arterial bleeding, especially the posterior part. Initial treatment, including chest tubedrainage insertion, is needed to avoid lung compression and to assess future treatment needed. Purpose: To report the patient survival from massive hemothorax caused by penetratingThoracic injury caused by an air rifle, treated by chest tube insertion and posterolateralthoracotomy to take out the bullet several days after.Case Report: 70-year male patient came to the Emergency Room (ER) Adihusada HospitalSurabaya with a penetrating chest injury caused by an air rifle on the right side of the chest. The patient had chest pain, shortness of breath, and hypoxia. By inserting a chest tube,emergency management was done by a general surgeon due to the massive right hemothorax.An immediate chest tube insertion was needed to overcome the patient’s breathing problem toassess the future treatment needed. Chest X-ray and CT-Scan was done immediately after thepatient’s hemodynamic were stable. Three days after hospitalizing, the Cardiothoracic andvascular surgeon performed posterolateral thoracotomy to take the bullet out of the chest.Conclusion: Seven days postoperatively, the patient was discharged from the hospital withoutany complications and stable hemodynamic. The patient went to the outpatient department forfollow-up one week after.